Take and give learning model during covid on students' learning outcomes in high school on ecosystem materials? - Apriliana Dwi Putri; Adeng Slamet; Meilinda Meilinda (STKIP Persada Khatulistiwa Sintang, 2021)
Covid-19 has a big impact on the world of education so that face-to-face learning is directly replaced by virtual learning by using learning applications. The research was aimed to determine the influence of the Take and Give model on the learning outcomes of the ecosystem materials of Az-Zahra Islamic High School students grade X. The research was conducted using a quasi-experimental method. Sampling from class X IPA was conducted equality test and random sampling technique. The cognitive learning instrument consisted of 20 multiple choice questions with five alternative answers that had a reliability score was 0.81. Research instruments were conducted validity tests and reliability tests. Analysis of hypothetical data was conducted using analysis of covariance (ANCOVA) test obtained result was 0.000 that stated that there was an influence on the students' cognitive learning outcomes that given the take and give model based on virtual. The results showed that the influence of taking and give learning models based on virtual learning had a significant impact on the students' learning outcomes grade X on ecosystem materials, which were shown in the final test scores of the experimental class which was 82,500 with a high category n-gain percentage was 52.8 and control class which was 76,111 with a moderate category n-gain percentage was 86.1. Based on research that applied the take and gives model can improve students' learning outcomes.Keywords: Take and give model, learning outcomes, attitude, ecosystem materials